Ang Espasyo ng Calle Colon sa Pagbubuo ng Pagkataong Cebuano, 1860-1942 - Obias, Rhodalyn W. (Philippine Social Sciences Review; Volume 64, No. 2, July-Dec 2012, Ed. Rolando C. Esteban, 2014)
Narratives about Colon street in Cebu City serve to strengthen a popular view of the street as the “oldest street” in the Philippines. However, why does Colon remain valuable to the Cebuanos? What can be drawn from the history of this old street that continues to be remembered and valued by the Cebuano? Why does Colon remain distinct in the consciousness of the Cebuanos? More than the physical aspect of Colon, each corner and building in the street speaks of a story that continues to be relevant and serves as a foundation of being Cebuano. Colon is not simply a place or a backdrop that holds and contains Cebuano experiences in the past; rather, it is an important space that actively forms, shapes, and express Cebuano identity. With this view, this study aims to analyze Colon as a unique Cebuano space by describing the structures found in Colon from 1860 to 1942, particular the old houses and theaters, and relating these to the various narrations that gave color and life to the street.
Keywords: Cebuano, Calle Colon